2021
DOI: 10.3390/jcm10235703
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Cardiothoracic Ratio as a Potential Predictor of Right Ventricular Enlargement in Patients with Suspected Pulmonary Embolism Due to COVID-19

Abstract: The aim of the study was to determine the usefulness of the radiological cardiothoracic ratio (CTR) as a predictor of right ventricular enlargement in patients with suspected pulmonary embolism during COVID-19. The study group consisted of 61 patients with confirmed COVID-19, suspected of pulmonary embolism based on physical examination and laboratory tests (age: 67.18 ± 12.47 years). Computed tomography angiography (CTA) of pulmonary arteries and chest radiograph in AP projection with cardiothoracic ratio ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This is another finding of our research on the predictive suitability of CTR. We previously demonstrated that in patients with suspected pulmonary embolism during COVID-19, CRT can be considered as a prognostic factor for right ventricular enlargement, especially as a negative predictor of right ventricular enlargement in the case of lower CTR values [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is another finding of our research on the predictive suitability of CTR. We previously demonstrated that in patients with suspected pulmonary embolism during COVID-19, CRT can be considered as a prognostic factor for right ventricular enlargement, especially as a negative predictor of right ventricular enlargement in the case of lower CTR values [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, identifying factors explaining the discrepancies between chest radiograph parameters and CMR-LVH may improve diagnostic abilities. For example, right ventricular enlargement may cause greater TCD and CTR measures [40][41][42]. In a study of heart failure patients, Fukuta et al revealed that increased CTR correlated more strongly with the size of the right ventricle than LV [41].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of heart failure patients, Fukuta et al revealed that increased CTR correlated more strongly with the size of the right ventricle than LV [41]. Recently, it has also been demonstrated that CTR could play a role in predicting right ventricular enlargement in patients with suspected pulmonary embolism during COVID-19 [42]. Elevation of the diaphragm due to high BMI can place the heart in a more horizontal position leading to an increase of TCD and CTR.…”
Section: Discussionmentioning
confidence: 99%